Notes on Trade in Varanus macraei in response to (Arida et al., 2021): ‘The Hunt for the Blue tree monitor on Batanta Island, Indonesia: Subsistence on a Treasure?’ - Chris R. Shepherd (The Ethnobiological Society of Indonesia, 2022)
The international wildlife trade is a growing threat to an increasingly long list of species, with reptiles among the most heavily impacted. Indonesia is a major source of many reptile species traded internationally, live to meet the demand for pets. Among the many endemic reptile species sought after is the blue tree monitor Varanus macraei. This species is captured from the wild in violation of Indonesia’s harvest and trade quotas which are set annually in an attempt to allow for sustainable use and at the same time protect species from over-exploitation. As this species is becoming increasingly difficult to obtain from the wild, it is clear that not only is the removal of specimens from the wild illegal, but it also appears to be unsustainable.